ANALISIS PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PD BPR BANTUL - Beta Asteria; Achmad Nurkholis (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
This study aims to determine how much influence motivation and work discipline on the performance of PD BPR Bantul employees partially or simultaneously. The method used in this research is quantitative method, where data collection uses questionnaires. The sample in this study amounted to 78 employees, where these employees served in PD BPR Bantul. Validity test which shows that the statement in this study is valid, while the reliability test using Cronbach Alpha is declared reliable. This research uses multiple linear regression analysis . The results of this analysis show that: (1) training has a positive effect on employee performance by 0.318. (2) work motivation has a positive effect on employee performance by 0.334.